Causes and Profiles Pertaining to the Emergency Room Admission of Stage V Chronic Kidney Disease Patients Undergoing Regular Hemodialysis at a Tertiary Hospital in Surabaya, Indonesia - Hani, Farahdhila; Aditiawardana; Atika (Current Internal Medicine Research and Practice Surabaya Journal, 2025)
Introduction: Chronic kidney disease (CKD) is characterized by decreased kidney function, with a glomerular filtration rate below 60 mL/min/1.73 m² persisting for at least three months. Hemodialysis is a common therapy for stage V CKD, yet complications may arise requiring emergency treatment. This study aimed to elucidate the causes and profiles of stage V CKD patients on regular hemodialysis who were admitted to the Emergency Department of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: A retrospective cross-sectional design and purposive sampling were used in this descriptive observational study. A univariate analysis was conducted on data collected from 72 stage V CKD patients who underwent regular hemodialysis and were admitted to the emergency room between January and March 2023. The inclusion criteria comprised stage V CKD patients undergoing regular hemodialysis in the emergency room. Patients with incomplete medical records were excluded. The collected data encompassed patients' age, sex, hemodialysis duration, interdialytic weight gain (IDWG), comorbidities, and complications. Results: Among the 72 patients, the predominant demographic was male (51.4%), primarily aged 56–65 years (30.6%), with a hemodialysis duration of ≤12 months (65.3%), an IDWG of 1–2 kg (16.7%), and hypertension (54.2%). The complications leading to patient admission in the emergency room mostly included anemia (77.8%), metabolic acidosis (54.2%), urinary tract infection (23.6%), hyperkalemia (19.4%), pulmonary edema (18.1%), and pneumonia (18.1%). Conclusion: Stage V CKD patients on regular hemodialysis are primarily admitted to the emergency room due to complications, including anemia, metabolic acidosis, urinary tract infections, hyperkalemia, pulmonary edema, and pneumonia.   Highlights: 1. Since almost all patients with stage V chronic kidney disease (CKD) undergo routine hemodialysis, it is important to assess its associated complications to help improve patient outcomes. 2. This study reports the prevalence of comorbid diseases and the diagnostic outcomes of patients experiencing complications in the Emergency Department of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. 3. The findings of this study provide valuable insights to patients, researchers, and future medical personnel regarding the characteristics of stage V CKD patients who regularly undergo hemodialysis and present to the emergency room.